(3GdfaMGJ GdYWQIs - (3MGeO, YKeGf GdTjN YHO Gddg MGLs; (3CMeO, SjO GdegOis; (3EHQGgje, NGdO YHO GdQMefs; (3GdSjO, fGHQi CMeO eMeOs; (3MOGO, cGed NGdOs ((3OHis (3eQcR eYdheGJ OHi dSHGb GdNjds, 2001)
(3GdcJGH jJfGhd eG jge cd eSde ai YHGOJg hMjGJg HESdhH ejSQ ajJfGhd eSGFd GdJhMjO hGdUdGI hGdWgGQI hZjQgGs
(3GdeMJhjGJ (B: (3GdJhMjO(B--(3GdWgGQI(B--(3GdUdGI(B--(3GdJUhas
Hurg
5
Keywords: (3GdUdGIs; (3GdWgGQIs; (3GdYHGOGJs; (3Gdabg GdESdGeis; (3GdhVhAs; (3Yde GdcdGes